In vitro plant regeneration system from cotyledon of Chinese cabbage (Brassica campestris ssp. chinensis L.) - XIE Jian-kun; CUI Hai-rui; SHU Qing-yao; XIA Ying-wu; SHOU Sen-yan (浙江大学学报. 农业与生命科学版)
The effects of factors including seedling age, different combinations of BA and NAA concentrations, Agar concentration, AgNO3 and GA3 on bud induction from cotyledon are analysed. The results indicate that the explants from 5-9 days old seedling are the most efficient to induce adventious buds. The concentration of BA is the key factor to adventious buds differentiation. BA lower than 2 mg/L, is harder to induce adventious buds. The combinations of 6 mg/L BA and 0.05 mg/L NAA can improve adventious buds induction. The culture medium with 12 g/L Agar, 5 mg/L AgNO3 and 2-3 mg/L GA3 can increase the frequence of differentiation. According to these results, a procedure for induction of adventious buds and regeneration system for Chinese cabbage is estabished. By using this system, high regeneration frequence can be obtained, but could be affected by genotypes.